1989
DOI: 10.1007/bf02670104
|View full text |Cite
|
Sign up to set email alerts
|

EPA and DHA contents of encapsulated fish oil products

Abstract: Seventeen brands of encapsulated fish oil or fish oil concentrate products, purchased during the period 1984–88 over the counter in the United States United Kingdom or Canada, were analyzed for their mg contents of eicosapentaenoic (EPA) and docosahexaenoic (DHA) acids per g of capsule contents. The mg contents were determined with respect to methyl tricosanoate internal standard by gas liquid chromatography (GLC) on a SUPELCOWAX‐10 flexible fused silica capillary column. The alkyl ester and free fatty acid pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
14
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 8 publications
6
14
0
Order By: Relevance
“…Overall, these results are similar to previously published studies . A summary and comparison of the results in these studies is shown in Table .…”
Section: Resultssupporting
confidence: 91%
“…Overall, these results are similar to previously published studies . A summary and comparison of the results in these studies is shown in Table .…”
Section: Resultssupporting
confidence: 91%
“…a serving of mussels (100 g meat) will typically contain about 1 mg (1 IU) of a-tocopherol in combination with about 200 mg of combined eicosapentaenoic and docosahexaenoic acids (Ackman, unpublished observations). This is a very favorable ratio for fishery products (Kovacs et al 1978) and is comparable to that found in good quality fish oil capsule products (Ackman et al 1989). The latter often contain an added mixture of tocopherols of vegetable oil origin (Shukla and Perkins 1991).…”
Section: Discussionsupporting
confidence: 63%
“…As EPA will change into DHA in the EPA cascade, it is however unclear how much of EPA and DHA combined is needed to achieve maximum plasma levels. In fish oil the EPA concentration is usually about 60% and the DHA 40% [41]. In the product we used the DHA was about 22% of the EPA amount.…”
Section: Discussionmentioning
confidence: 99%